ANALISIS FAKTOR YANG MEMPENGARUHI PREFERENSI KONSUMEN DALAM PEMBELIAN FROZEN FOOD DI KOTA BATAM - Rika, Delvina; Purba, Tiurniari (SCIENTIA JOURNAL, 2021)
The purpose of this study was to determine the effect of brand and product quality on consumer preferences in purchasing frozen food in Batam City. The simple random sampling method was used and with slovin formula, 152 samples were needed for this study. Data was obtained through questionnaires distributed to the Taman Kota Mas Housing citizens which 202 respondents gathered. Data analysis was performed using multiple linear regression analysis. This study used SPSS software version 21 for testing. The validity and reliability tests was used as data quality test, whichthe classic assumption tests in this study used the normality test, the multicollinearity test and heteroscedasticity test and the effect test used multiple linear regression analysis and analysis of the coefficient of determination (R2), while the hypothesis testing in this study using the t test and the F test. The results showed that brand had a significant effect on consumer preferences and product quality also had a significant effect on consumer preferences. As of brand and product quality simultaneously had an effect on consumer preferences in purchasing frozen food in Batam City.